Earnings management practices between government linked and Chinese family linked companies - Jow, Wai Yen; Loo, Sin Chun; Zainal Abidin, Sazali; Amin Noordin, Bany Ariffin (Faculty of Economics and Management, Universiti Putra Malaysia, 2007)
This paper investigates the prevalence of earnings management between government linked companies (GLCs) and Chinese family linked companies (CFLCs). Information on twenty five companies from each ownership structure were collected, for the years 2004 to 2005.The findings reveal that GLCs have a tendency to manage their earnings upwards while CFLCs tend to adjust their earnings downwards. On average, GLCs appear to have a higher level of earnings management as compared to CFLCs. There is a weak evidence to show that the concentration of shareholdings in GLCs affect the extent of earnings management. This is however not observed among CFLCs. In general our results do not support the belief that higher concentration of shareholdings results in increased earnings management.